Gender Preferences in Job Vacancies and Workplace Gender Diversity - David Card; Fabrizio Colella; Rafael Lalive (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2023)
In spring 2005, the Ombud for Equal Treatment in Austria launched a campaign notifying employers and newspapers that gender preferences in job ads were illegal. At the time over 40% of vacancies on the nation's largest job board stated a gender preference; within a year the rate fell below 5%. We merge job board vacancies and employer records to study how the campaign affected hiring choices and the gender diversity of occupations and workplaces. Using pre-campaign data, we predict the use of gender preferences, then conduct a difference-indifferences analysis of hiring outcomes for vacancies with predicted male or female preferences, relative to those with no predicted preferences. The elimination of explicit gender preferences boosted the share of women hired for jobs that were likely to be targeted to men (and vice versa). At the firm level, we find that the campaign led to a rise in the share of women at firms that were more likely to use male SGP's, and a symmetric increase in the share of men at firms that were likely to use female SGP's, with no effects on firm survival, employment, or average wages.
Keywords: J16; J68; J63; 330; Gender Preferences; Gender Segregation; Anti-discrimination Policy